Promoting Active Lifestyle through Aerobic Gymnastics Award Scheme: 健美體操奬勵計劃推廣活躍生活模式 - CHEUNG, Siu Yin (Asian Journal of Physical Education & Recreation, 2008)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Aerobic gymnastics is a new discipline of the International Federation of Gymnastics. It consists of gymnastic movement elements and aerobics components. The aerobic gymnastics routine is a combination of movements which are about strength (power); static strength; jumping and leaping; flexibility; and the seven basic aerobics steps. The aims of the aerobic gymnastics award scheme are to encourage active lifestyle and develop generic skills for students in Hong Kong. 140 school teachers/ coaches successfully completed the teachers’ /coaches’ training courses and conducted the aerobic gymnastics courses in their schools. Fun days were also conducted so that students performed their aerobic gymnastics routines in front to their friends and parents. At the same time, physical fitness tests were conducted for students so as to understand their physical fitness levels. In addition, three aerobic gymnastics awards were designed for students and they were awarded certificates and badges after successfully completing the routines required. Moreover, the first inter-school sports aerobics competition was conducted in 2003. Over 500 students from 60 schools had taken part in the competitions since then and more than 4500 certificates and badges had been issued in 2002-03. Positive feedback was received from teachers and students. Aerobic gymnastics can promote active lifestyle and wellbeing. It can also enhance creativity cooperation, communication and teamwork for students. 健美體操是國際體操聯盟的一項新的體操項目，它包括體操及「有氧運動」的動作。一套健美操動作有肌力、跳、柔韌等動作和基本的「有氧運動」步伐。香港體操總會於二零零零年起推廣此項目並設計健美體操獎勵計劃。計劃的目的是鼓勵香港學生常做運動和發展學生的共通能力。一百四十多位教師及教練成功完成教師/教練培訓課程後 > 便在學校教授健美體操。同學們在同樂日中向父母及親友表演健美體操套路，同時，他們也可參與體適能測試，以了解自己的體適能水平。此外，同學可透過參與健美體操獎勵計劃以挑戰自己的技能。自二零零三年首次舉辦學界健美體操比賽，至今已有五百多位來自六十所學校的學生參與，並有近四千五百位學生考獲章別以作獎勵。健美體操能推廣活躍的生活模式，同時也可培養學生的創造、協作、溝通等共通能力和團隊精神。